Natural convection from a triangular array of isothermal horizontal cylinders - O'Shaughnessy, Seamus; Gibbons, Michael; Persoons, Tim; Murray, Darina (My University, 2021)
Natural convection heat transfer from three isothermally heated horizontal cylinders submerged in water in a triangular arrangement is investigated. Two configurations, named here as one over two and two over one, are characterised for three cylinder spacings ( = 2, 3 and 4 cylinder diameters) and Rayleigh number conditions ( = 2, 4 × 106 and 6 × 106). Combined local heat flux measurements and flow velocity measurements using particle image velocimetry are employed to examine the governing heat transfer mechanisms. For many cases of the one over two configuration, substantial differences from the single cylinder case are noted. The buoyant plumes generated from the two lower cylinders interact with the flow field and heat transfer around the upper cylinder, altering the local fluid velocities and temperature fields. This effect is dependent on both the inter-cylinder spacing and the Rayleigh number condition. For the two over one setup, both upper cylinders for all cases, except and = 6 × 106, behave in the same manner as a single cylinder. This is due to the competing effects of the buoyant plume rising from the lower cylinder and the restriction of flow through the gap between the two upper cylinders.
PUBLISHED
Keywords: Flow oscillations; Tubular heat exchangers; Natural convection; Particle image velocimetry; Thermal plume interaction; Tubular heat exchangers